Desirable qualities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
To be useful, and therefore to appeal to landless and usually poor people, animals should have most or all of certain attributes. They must: - provide one or more products which are already in local demand - be readily available - and foundation...